Análisis costo-beneficio de la aplicación de la señalización vial en el tramo de la Vía El Deseo-Cone - Palomino Alvarado, Carlos Arturo (2024)
The thesis "Cost-Benefit Analysis of the Application of Road Signage on the Section of the 'El Deseo-Cone' Road" evaluates the economic viability of improving signage on a specific section of road. The research is focused on determining whether the benefits of improved signage justify the associated costs. The study begins with an evaluation of the current state of signage on the El Deseo-Cone road, highlighting deficiencies such as insufficient and poorly visible signs, which contribute to an increase in accidents and related costs, including medical expenses and material damage. The investigation includes an analysis of the costs of installing and maintaining the new signage, as well as possible traffic disruptions during the process...........